Resolution [compact disc, unabridged] - Parker, Robert B., 1932-2010 (Random House Audio, 2008)
After a bloody confrontation in Appaloosa, Everett Hitch heads into the afternoon sun and ends up in Resolution, an Old West town so new the dust has yet to settle. He takes the job as lookout at Amos Wolfson's Blackfoot Saloon and quickly establishes his position as the protector of the ladies who work the back rooms. When greedy mine owner Eamon O'Malley threatens the loose coalition of local ranchers, Hitch finds himself in the middle of a makeshift war between O'Malley's men and the ranchers